A Novel Two‐Step Model to Investigate Turbulent Gas Flows Shearing Thin Liquid Films. Issue 1 (18th November 2019) - Bender, Achim; Stroh, Alexander; Frohnapfel, Bettina; Stephan, Peter; Gambaryan-Roisman, Tatiana
Abstract: In this work a two‐step model to investigate a thin liquid film sheared by a turbulent gas flow is presented. In a first step, a direct numerical simulation of the gas phase is conducted. The turbulent shear stress at the lower wall is stored and used as a boundary condition for the long‐wave evolution of the liquid film, which is calculated in a second step. Results show that the turbulent shear stress fluctuations have to be considered when evaluating turbulent‐two‐phase channel flows.